Siraya : Retrieving the Phonology, Grammar and Lexicon of a Dormant Formosan Language. - Adelaar, K. Alexander (Trends in linguistics. Documentation ;, 2011)
Siraya is a Formosan language with unique typological features once spoken around Tainan City in southwest Taiwan. This comprehensive study is based on an analysis of the language of the Siraya Gospel of St. Matthew, which was translated from the Dutch in 1661. It contains a grammar, lexicon and extensive text with interlinear glossing as well as an introduction with detailed background information.